Determining the Efficacy of Providing Ice Compression for Fitness Enhancement After Speed Endurance Exercise on Reducing Heart Rate, IL-6, and Fatigue Index in Football Athletes - Fajar, Muhammad Kharis; Hariyanto, Agus; Wahjuni, Endang Sri; Kartiko, Dwi Cahyo; Siantoro, Gigih; Phanpheng, Yanyong; Kusuma, I Dewa Made Aryananda Wijaya; Pramono, Bayu Agung; Rusdiawan, Afif; Pranoto, Adi (Physical Education Theory and Methodology, 2025)
Objectives. This study aimed to investigate the effects of Ice Compression For Fitness (ICEFIT) on reducing heart rate, Interleukin-6 (IL-6) levels, and fatigue index in soccer athletes after performing speed endurance training. Materials and methods. A total of 34 male students from the Football Coaching Department at the State University of Surabaya (Indonesia), aged 18-20 years, with a normal BMI, at least 10 years of football training experience, and no injuries in the past 6 months, were selected as research subjects and were given ICEFIT treatment for 4 weeks. Data collection was conducted by measuring heart rate, IL-6 levels, and fatigue index at both the pre- and post-intervention stages. Data analysis techniques included using the parametric paired sample t-test and independent sample t-test, with a significance level of 5 %. Results. The results showed that ICEFIT significantly reduced heart rate, IL-6 levels, and fatigue index in soccer athletes after speed endurance training (p ≤ 0.05). Furthermore, marked reductions in heart rate, IL-6 levels and fatigue index were observed between the groups (p ≤ 0.05). Conclusions. These findings demonstrate that ICEFIT is effective in reducing heart rate, IL-6 levels, and fatigue index in soccer athletes after speed endurance training.